Self-care skills between institutionalised and home dwelling older adults : a preliminary study - Nor Afifi Razaob,; Masne Kadar,; Hanif Farhan Mohd Rasdi,; Farahiyah Wan Yunus,; Nor Azwani Mohamed Bukhori,; Tham, Si Yan; Chai, Siaw Chui (Penerbit Universiti Kebangsaan Malaysia, 2021)
Self-care is defined as activities performed by individuals, families, and communities to enhance their health, prevent diseases, limit illnesses, and restore health. Previous research has mainly focused on self-care skills of older adults in either institution or residential homes separately but limited studies have compared between both these settings. This study aimed to compare the self-care skills between institutionalised and home dwelling older adults at selected area in Malaysia. A total of 43 participants aged 60 years old and above were recruited in our study; (23 participants were home-dwelled older adults and 19 participants were recruited from institutionalised older adults located in Kuala Lumpur). The Malay Version of Performance Assessment of Self-Care Skills (M-PASS-HOME) 4.0 was used focusing on four main subtests of self-skills; oral hygiene, trimming toenails, house mobility and shower mobility. The differences in self-care skills between institutionalised and home dwelling older adults are statistically significant (p<0.01) in the aspects of independency for all self-care activities. The results of this study revealed that home dwelling older adults group are more independent in self-care activities of oral hygiene, trimming toenails, house mobility and shower mobility compared to institutionalised group.